PENERAPAN RADIO-FREQUENCY IDENTIFICATION (RFID) PASIF UNTUK IDENTIFIKASI RESPON TIME PERAWAT PADA MANAJEMEN SISTEM PELAYANAN RUMAH SAKIT - Hadi Aryadi Salamet; Agung Wibowo; Didik Indrayana (Swabumi, 2015)
Respon time of nursery services is a part that plays an important role in hospitals, namely publichealth services, including nursing services based on the response time, in the form of service ofmedical treatment in hospitals, of course it has been and should be realized, if a service will befulfilled because it has a work rules agreed, but this is still less effective because there are severalother factors, one of which the nature of each individual are different to the rules applicable.Appeared an idea to develop a call using the tool identification system by implementing passiveRadio Frequency Identification (RFID) which is a compact wireless technology. The RFIDtransmitter in nurse tag name will respond back to give further information about the card readerto be read by the system at the minimum Arduino to do the identification process. Each call willonly stop if a nurse had done the scan ID cards at the RFID reader at the patient's room. RFIDcan provide efficient services that can quickly scan process gives a sense of security to patients,because every nurse who handles patients had identity card identifier embedded in it have an ID(identity) on the card.